AB0201 Cell Surface Expression of DNAM-1 (CD226) on CD8+ T Cells is Increased in Patients with Systemic Sclerosis. (10th June 2014) - Ayano, M.; Tsukamoto, H.; Tanaka, A.; Nakano, S.; Ueki, N.; Ueda, S.; Hisamoto, S.; Ota, S.-I.; Akahoshi, M.; Arinobu, Y.; Niiro, H.; Horiuchi, T.; et al.
Abstract : Background: DNAM-1 (CD226) is well known as a genetic risk factor of many autoimmune diseases such as systemic sclerosis (SSc). More recently, Avouac et al. have reported that mice deficient for DNAM-1 are protected from bleomycin-induced dermal fibrosis. In human, however, the roles of DNAM-1 in SSc are still unknown. Objectives: To evaluate cell surface expression of DNAM-1 on peripheral blood lymphocytes from SSc patients and to identify the roles of DNAM-1 in the pathogenesis of SSc. Methods: The expression of DNAM-1 was analyzed by flow cytometry (FCM) on surface of CD4+ T cells, CD8+ T cells and CD19+ B cells from 41 SSc patients (median age, 59 years; female, 37) and 23 healthy controls (HCs). We evaluated the relationship between DNAM-1 expression level on CD8+ T cells and clinical manifestations of SSc. Intracellular and extracellular cytokine production in CD8+ T cells with or without DNAM-1 was measured by FCM (intracellular staining and multiplex bead array, respectively) after stimulation with PMA/Ionomycin. The cytotoxic capacity of CD8+ T cells against human umbilical vein endothelial cells (HUVECs) was assessed in the presence or absence of anti-DNAM-1 neutralizing antibody in SSc patients and HCs. Results: The proportion of DNAM-1 high CD8+ T cells was increased in SSc patients (median, 52.5%) compared to HCs (29.7%, P=0.0002). We found no significant difference between SSc patients and HCs in CD4+ T cells and CD19+ B cells. The expression of DNAM-1 on CD8+ T cells was higher in patients with diffuse cutaneous subtype than those with limited cutaneous subtype (P=0.0009) and was higher in those with interstitial pneumonia than those without (P=0.0016). The percentage of DNAM-1 high CD8+ T cells was significantly correlated with modified Rodnan skin thickness score (r =0.4295, P=0.0071). The production of IL-13 was significantly increased in DNAM-1 positive CD8+ T cells compared with DNAM-1 negative ones and the neutralization of DNAM-1 impaired the IL-13 production from CD8+ T cells. The cytotoxic ability of CD8+ T cells was significantly elevated in SSc patients and positively correlated with the percentage of DNAM-1 high CD8+ T cells. The cytotoxicity against HUVECs was partially inhibited in the presence of anti-DNAM-1 neutralizing antibody. Conclusions: These findings indicate that DNAM-1 high CD8+ T cells are involved in the pathogenesis of SSc via the production of profibrotic IL-13 and endothelial cell injury. References: Avouac J, Elhai M, Tomcik M, et al. Critical role of the adhesion receptor DNAX accessory molecule-1 (DNAM-1) in the development of inflammation-driven dermal fibrosis in a mouse model of systemic sclerosis. Ann Rheum Dis. 2013;72:1089-98. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3217